Plasma-arc cutting control : investigations into machine vision, modelling and cutting head kinematics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatu, New Zealand - Flemmer, Mathew (Massey University, 2018)
Plasma-arc cutting (PAC) is widely used in industry, but it is an under-researched fabrication tool. A review of the literature reveals much study is needed to improve the PAC process regarding efficiency, quality, stability and accuracy. This research investigated a novel control method for PAC. The PAC process was investigated to identify the gaps, and develop feasible methods, methodologies and systems to improve the PAC cutting quality and process control using machine vision. An automated, visual-inspection algorithm was successfully developed. The algorithm uses NC code to path plan and perform kerf width measurement. This visual inspection facilitated research into several aspects of PAC such as the extent of radiative heat transfer, the significance of kerf asymmetry, and a model describing the slope of the leading edge of the kerf-with respect to feed rate and material thickness. A kinematic investigation was conducted on 3 bevel capable plasma heads to complete the elements of a novel control method. An automated, visual-inspection (AVI) system for PAC was designed that consists of a vision unit and a mounting rig. This system is able to perform real-time, kerf width measurement reaching an accuracy of 0.1mm. The methodology was validated by experiment, testing cuts on parts with varying size, shape and complexity. The outcomes of this research were published in the International Journal of Mechanical and Production Engineering and the proceedings of the 2017 Mechatronics and Machine Vision in Practice (M2VIP) international conference. With this developed vision rig, further research was conducted such as an empirical investigation into the relationship between kerf angle and kerf width with respect to torch height, feed rate and material thickness. This investigation was comprised of 35 combinations of the process parameters with 9 replicates for each. A relationship between the process parameters and quality measures was developed, and the magnitudes of kerf asymmetries were quantified. The understanding of the phenomenology of PAC is deficient in several areas. An experimental study was undertaken that reduced the effects of heat transfer by conduction and convection in order to estimate the contribution by radiative heat transfer. This experimental study maintained an arc between a water-cooled anode and plasma torch for 15 seconds. A test piece was specifically designed with imbedded, resistance-temperature-device thermometers positioned around the transferred arc and the temperature was measured. This investigation was able to estimate the effects of radiation from the plasma-arc. The study found radiative heat transfer is less than 3% of the total power input. Another experimental study obtained information on the shape of the leading edge of the kerf. For this study slots were cut into steel plates of 6, 8 and 10mm thickness, at feed rates between 350 and 2000mm/min with a torch height of 1.5mm. Edge points for the centre axis of the leading profile were obtained. A relationship between surface angle and material thickness and feed rate was established and is validated through the test range. A study on obtaining cutting profile data on the front face of the kerf was also undertaken. Slots were cut into plates of 6 and 10mm thickness. Edge points were obtained for the front 180 degrees of the kerf face at sections in 2mm increments. A 3D representation of the shape of the face was then able to be presented. Finally, the kinematics for 3 bevel capable PAC heads was developed. Two of the heads are existing industrial heads, and the third head is being developed by Kerf Ltd. The kinematics investigation produced the DH parameters and transformation matrices for the forwards kinematics. These were validated using MATLAB®. The resulting dynamics were also produced. In conclusion, PAC is a complicated process. This research carried out several studies and has addressed several literature gaps with the proposed methods, methodologies and systems, developed through machine vision and PAC head kinematic study. This research was funded by Callaghan Innovation PhD research funding and received financial support from Kerf Ltd. Callaghan Innovation is a New Zealand government research funding body. Kerf Ltd. is a New Zealand PAC machine manufacturer and distributor.
Figures 2.2 to 2.6 have been removed for copyright reasons but may be accessed via their source listed in the References: Fig 2.2 = Fig 1 Giraud et al., 2006; Fig 2.3 = Fig 1 Colt, 2015; Fig 2.4 = Fig 7 Freton et al., 2003; Fig 2.5 = Fig 7 Colombo et al., 2009 & Fig 2.6 = Fig 8 Giraud et al., 2006.
Keywords: Cutting machines; Machining; Automation; Machine-tools; Numerical control; Computer vision; Industrial applications; Quality control; Optical methods